Coping with COVID-19 in a non-democratic system: Policy lessons from Thailand’s centralised government - Piyapong Boossabong; Pobsook Chamchong (International Review of Public Policy)
Policy analysis in Thailand during these turbulent times (COVID-19) is based mainly on expert opinion expressed under a highly centralised and non-democratic political system. However, the government’s claim of scientific rationality shows that political reasons are at play behind the scenes. Moreover, this policy domain does not interact well with the social domain as it is missing the social, contextual and experiential constructions of policy problems and solutions. Scientists are less sensitive to the social mood and fears and are thus unable to cope effectively with the psychological impact of the crisis. The static governmental mechanism also fails to work well with existing organic and flexible governance practices at a local level. This article thus suggests the importance of underscoring the need for efforts to decentralise and re-democratise political systems and suggests the practice of ‘safety participation’ to better articulate and integrate the essential relationships between science, politics and citizens.